USE OF ARTIFICIAL INTELLIGENCE FOR WORK SAFETY MANAGEMENT - Krainiuk, O.; Buts, Yu.; Barbashyn, V.; Yatsiuk, M. (Municipal economy of cities. Series: «Economy science», 2023)
Artificial intelligence introduces innovations in the field of monitoring, diagnostics, and management in the production environment, allowing for reducing the risks of industrial accidents, improving the quality of work, and contributing to the increase of production efficiency. The article considers the main aspects of the application of artificial intelligence for security at enterprises, explores various methods and technologies, and analyses examples of successful implementations in various industries. We also discuss the challenges and prospects related to this topic and closely examine the impact of artificial intelligence on the future of industrial safety. The article aims to study the possibilities of artificial intelligence for solving labour safety problems. The task is to evaluate the potential areas of implementation and algorithms of neural networks, which could reduce the number of dangerous factors associated with human activity at work and increase the level of occupational safety. With the use of AI, numerous innovative solutions can be created to improve control, predict potential hazards, and reduce risks to workers and equipment. Currently, neural networks are successfully used in the fields of production and labour protection to ensure visual control of compliance with safety measures. An indisputable advantage is the sustainability of monitoring and the exclusion of the human factor from this process. Artificial intelligence allows us to warn of situations related to injuries and non-compliance with safety rules, as well as track potentially dangerous events in any area of production. Machine vision, a crucial component of artificial intelligence, enhances workplace safety through continuous monitoring, anomaly detection, personnel identification, equipment evaluation, visual training, and video analysis. It improves safety conditions and mitigates risks effectively. Artificial intelligence and AI-powered voice systems are becoming crucial tools for enhancing workplace safety. They aid in preventing industrial accidents, optimising work processes, and innovating safety control and prediction solutions. AI plays a vital role in visual safety monitoring and eliminates the human factor, ensuring reliability and efficiency.